Micropropagation of Medicinal Plants: a Review - Chatterjee, Tuhin; Ghosh, Biswajit (International Journal of Economic Plants, 2020)
Well developedmethods are presently available to help growers meet the demand of the pharmaceutical industry in the next century. Micropropagation of medicinal plants is extensively used to produce active compounds for herbal and pharmaceutical industries. Population growth, urbanization, climate change and unrestricted collection of medicinal plants from nature are resulting in an over- exploitation as well as habit destruction of wild resources of medicinal plants. Conservation of genetic materials of many vulnerable medicinal plants also involves culturing techniques. Micropropagation protocols have been developed for a wide range of medicinal plants, which includes endangered and vulnerable plant species. This review only describes the role of in vitro propagation techniques in medicinal plants.